Compositional and functional succession of bacterial and fungal communities is associated with changes in abiotic properties during pig manure composting. (15th July 2021) - Wang, Xiaofang; Wan, Jinxin; Jiang, Gaofei; Yang, Tianjie; Banerjee, Samiran; Wei, Zhong; Mei, Xinlan; Friman, Ville-Petri; Xu, Yangchun; Shen, Qirong
Highlights: Organic matter degradation and humification point to the maturation of compost. Bacillales, Eurotiales and Glomerellales dominate bacterial and fungal communities. Function of bacterial metabolism and fungal saprotroph jointly dominate composting. Microbial community changed greatly at the second thermophilic period. Synergistic effect of bacteria and fungi may depend on their metabolite exchange. Abstract: While both bacteria and fungi are important for the degradation and humification of organic matter during composting, it is unclear to what extent their roles are associated with abiotic compost properties. This study evaluated changes in abiotic compost properties and the succession of bacterial and fungal communities during pig manure composting for 90 days. The compost rapidly reached thermophilic phase (>58 ℃), which lasted for 15 days. Both bacterial and fungal community compositions changed drastically during composting and while bacterial diversity increased, the fungal diversity decreased during the thermophilic phase of composting. Two taxa dominated both bacterial ( Bacillales and Clostridiales ) and fungal ( Eurotiales and Glomerellales ) communities and these showed alternating abundance fluctuations following different phases of composting. The abundance fluctuations of most dominant bacterial and fungal taxa could be further associated with decreases in the concentrations of fulvic acid, cellulose, hemicellulose and overall biodegradation potential in the compost. Moreover, bacterial predicted metabolic gene abundances dominated the first three phases of composting, while predicted fungal saprotrophic functional genes increased consistently, reaching highest abundances towards the end of composting. Finally, redundancy analysis (RDA) showed that changes in abiotic compost properties correlated with the bacterial community diversity and carbohydrate metabolism and fungal wood saprotrophic function. Together these results suggests that bacterial and fungal community succession was associated with temporal changes in abiotic compost properties, potentially explaining alternating taxa abundance patterns during pig manure composting.